1991
DOI: 10.1203/00006450-199103000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Erythrocyte Superoxide Dismutase Activity in Low Birth Weight Infants Given Iron Supplements

Abstract: ABSTRAU. Erythrocyte superoxide dismutase (ESOD) activity reflects copper utilization and the risk of copper deficiency. To investigate the possible effects of inorganic iron on the metabolism of copper in low birth weight infants, we have measured ESOD activities in three groups of infants receiving different iron supplements. Fifty-five low birth weight infants were randomly assigned to receive daily from 28 d either 13.8 mg (HiFe), 7 mg (MidFe), or no elemental iron (NatFe) as iron edetate. At 27 d, 8, 12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…The earlier study in term SGA infants also reported similar findings. 10 Some preterm trials documented a significant improvement in serum ferritin, 13 whereas others had no significant change or did not estimate ferritin. 9 10 We did not document any benefit in anthropometry; the inadequate duration of follow up and small sample size however preclude any definite conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier study in term SGA infants also reported similar findings. 10 Some preterm trials documented a significant improvement in serum ferritin, 13 whereas others had no significant change or did not estimate ferritin. 9 10 We did not document any benefit in anthropometry; the inadequate duration of follow up and small sample size however preclude any definite conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is recommended that premature infants receive at least 2-4 mg/kg/d of iron to prevent iron deficiency anemia (25), high amounts of iron added to the diet have been shown to decrease serum ceruloplasmin (26) and copper-zinc SOD levels in erythrocytes (27). These effects may be the result of adverse effects on copper metabolism from excess iron.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Barclay et al [33] found no effect on hemoglobin of an iron intake of 3.6-6.8 mg/kg/day as compared to 1.0-1.6 mg/kg/day from 2 to 30 weeks postnatal age in infants with an average birth weight of 2,000 g. However, there was a lower erythrocyte superoxide dismutase activity in the high iron group, suggesting altered copper metabolism -a possible adverse effect of iron [33] .…”
Section: Effects Of Interventionsmentioning
confidence: 99%